Mossbauer analysis of the structure Fe-Ni-C alloys after heat and ultrasonic treatments - Nadutov, V.M.; Semenov, D.V.; Svystunov, Ye.O.; Kuzmich, G.I. (Functional Materials, 2004)
Mossbauer spectroscopy has been used for atomic scale investigation of austenitic Fe-Ni-C alloys after ultrasonic and low-frequency impact surface treatments. The phase composition and hyperfine structure of the Fe-30.5 % Ni—1.5 %C and Fe-25.3 %Ni-0.78 %C alloys with the f.c.c. lattice after annealing at 1373 K and 773 K in vacuum and following ultrasonic surface treatment (UST, f = 1—3 kHz, the amplitude 20 pm, t = 8— 24 s) have been studied. The results were analyzed in comparison with the low-frequency impact surface treatment (1ST) of the alloys. The microhardness of the alloys after UST has been analyzed. Мессбауэровская спектроскопия использована для исследования на атомном уровне аустенитных Fe-Ni-C сплавов после ультразвуковой и низкочастотной ударной поверхностной обработок. Изучен фазовый состав и сверхтонкая структура ГЦК сплавов Fe-30.5 % Ni—1.5 %C и Fe-25.3 % Ni—0.78 %C после нагрева до 1373 К и 773 К в вакууме и последующей ударной ультразвуковой обработки (УЗО), f = 1-3 кГц, амплитуда 20 мкм, t = 8-24 с. Результаты проанализированы в сравнении с влиянием низкочастотной ударной поверхностной обработки (УПО) сплавов. После УЗО проанализирована микротвердость сплавов. Mecc6ayepiBCbKy спектроскопію використано для дослідження на атомному рівні аустенітних Fe-Ni-C сплавів після ультразвукової та низькочастотної ударної поверхневої обробок. Вивчено фазовий склад і надтонку структуру ГЦК сплавів Fe-30.5 %Ni-1.5 %C та Fe-25.3 % Ni—0.78 %C після нагрівання до 1373 К і 773 К у вакуумі та наступної ударної ультразвукової обробки (УЗО) (f = 1-3 кГц, амплітуда 20 мкм, t = 8-24 с). Результати проаналізовано у порівнянні з впливом низькочастотної ударної поверхневої обробки (УПО) сплавів. Після УЗО проаналізована мікротвердість сплавів.